Otra empresa es posible, propuestas y experiencias desde la economía social (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2012)
The crisis we are going through has revealed serious systemic inconsistencies and risks. Insistently from different perspectives, a change in the economic model isrequested, in its values and functioning principles. An urgent need to introduce,among others, new dimensions: ethics, social responsibility, sustainability and a wellunderstood long term approach, is demanded. Social Economy and Cooperativism have been proposing for a long time a different business model which stimulates asustainable, more balanced and fair development, based on social and environmental values.
Keywords: crisis; values; cooperatives; social economy; ethics and sustainability.